2020
DOI: 10.1007/s00167-020-05859-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular injection of bone marrow-derived mesenchymal stem cells enhances regeneration in knee osteoarthritis

Abstract: Purpose This review aimed to evaluate the efficacy of intra-articular injections of bone marrow derived mesenchymal stem cells (BM-MSCs) for the treatment of knee osteoarthritis (KOA). Methods This narrative review evaluates recent English language clinical data and published research articles between 2014 and 2019. Key word search strings of ((("bone marrow-derived mesenchymal stem cell" OR "bone marrow mesenchymal stromal cell" OR "bone marrow stromal cell")) AND ("osteoarthritis" OR "knee osteoarthritis")) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 67 publications
1
39
0
2
Order By: Relevance
“…The data of the research included in this meta-analysis are detailed and meet the minimum reporting requirements agreed by experts. 37 We found that MSC-based therapy is safe. Joint pain or swelling after injection may diminish over time or following oral medication.…”
Section: Discussionmentioning
confidence: 81%
“…The data of the research included in this meta-analysis are detailed and meet the minimum reporting requirements agreed by experts. 37 We found that MSC-based therapy is safe. Joint pain or swelling after injection may diminish over time or following oral medication.…”
Section: Discussionmentioning
confidence: 81%
“…Dear Editor, Stem cell therapy has been investigated by a number of basic, pre-clinical and clinical studies, and these studies have proved that stem cells are safe and effective in the treatment of many medical conditions and diseases. (1)(2)(3)(4) A study including 10 patients with confirmed diagnosis for coronavirus 2019 (COVID-19), and pneumonia due to infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), reported significant improvement in symptoms of all patients treated with mesenchymal stem cells (MSCs) with no adverse effects. Of these patients, 7 were treated with intravenous concentration of 1x10 6 cells per kilogram of body weight and 3 were treated with placebo.…”
Section: Doi: 1031744/einstein_journal/2020ce5802mentioning
confidence: 99%
“…However, the benefits are limited to advanced OA, and are not considered a long-term solution. 9 Therefore, it is very important to explore new therapeutic methods for the treatment and prevention of OA.…”
Section: Introductionmentioning
confidence: 99%